Women’s Leadership in Educational Institutions: A Qualitative Literature Review on Challenges and Strategic Opportunities - Hartinah; Thamrin, Putri Aulia; Ilahi, Muhammad Nur Ilham; Fitriani; Angkananon, Chumphon (Journal of Islamic Education Research, 2025)
Women leaders in education continue to face structural and cultural barriers, such as biased recruitment and leadership stereotypes tied to masculinity. However, their collaborative, empathetic, and inclusive leadership style offers unique advantages in building responsive and innovative educational environments. This qualitative literature review explores studies, policies, and best practices related to women's leadership in educational institutions. The findings reveal that gender quotas, leadership training, and mentoring programs effectively increase women’s access to strategic roles. Mentoring also boosts confidence and expands professional networks. To empower women as transformative leaders, institutions must adopt inclusive policies, support mentoring initiatives, and challenge gendered cultural norms. Strengthening women’s leadership can improve institutional equity, innovation, and sustainability. Pemimpin perempuan di bidang pendidikan masih menghadapi hambatan struktural dan kultural, seperti bias dalam rekrutmen serta stereotip bahwa kepemimpinan adalah sifat maskulin. Namun, gaya kepemimpinan perempuan yang kolaboratif, empatik, dan inklusif memiliki keunggulan dalam menciptakan lingkungan pendidikan yang adaptif dan inovatif. Studi pustaka ini menggunakan pendekatan kualitatif untuk menelaah berbagai penelitian, kebijakan, dan praktik terbaik terkait kepemimpinan perempuan. Hasil menunjukkan bahwa kuota gender, pelatihan kepemimpinan, dan program mentoring efektif meningkatkan akses perempuan ke posisi strategis. Mentoring juga memperkuat kepercayaan diri dan jaringan profesional. Untuk memberdayakan perempuan sebagai pemimpin transformatif, institusi perlu menerapkan kebijakan inklusif, mendukung program mentoring, dan menantang norma budaya yang bias gender. Penguatan kepemimpinan perempuan akan mendorong kesetaraan, inovasi, dan keberlanjutan institusi pendidikan.